Comparative proteomics analysis reveals the domesticated Lepista sordida primordium differentiation regulation mechanism and the subsequent different development patterns in the pileus and stipe - Xiuqing Yang; Meijie Liu; Yanjiao Zhang; Lizhong Guo; Junqi Wang; Sizhu Li; Yan Zhang; Xiaobo Li; Lili Xu; Hao Yu (Food Science and Human Wellness, 2024)
The wild Lepista sordida is a kind of precious and rare edible fungus. An excellent strain of it by artificial domestication was obtained, which was high-yield and high in iron content. In this study, high-throughput comparative proteomics was used to reveal the regulatory mechanism of its primordium differentiation in the early fruiting body formation. The mycelium before the primordium differentiation mainly expressed high levels of mitochondrial functional proteins and carbon dioxide concentration regulatory proteins. In young mushrooms, the highly expressed proteins were mainly involved in cell component generation, cell proliferation, nitrogen compound metabolism, nucleotide metabolism, glutathione metabolism, and purine metabolism. The differential regulation patterns of pileus and stipe growth to maturity were also revealed. The highly expressed proteins related to transcription, RNA splicing, the production of various organelles, DNA conformational change, nucleosome organization, protein processing, maturation and transport, and cell detoxification regulated the pileus development and maturity. The proteins related to carbohydrate and energy metabolism, large amounts of obsolete cytoplasmic parts, nutrient deprivation, and external stimuli regulated the stipe development and maturity. Multiple CAZymes regulated nutrient absorption, morphogenesis, spore production, stress response, and other life activities at different growth and development stages.